(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article has explored the theoretical bases and practical problems of assessment of enterprises solvency, which users of techniques, developed by relevant ministries and agencies and mandatory use of entities (called typical or common) deal with. Despite their different purposes (the risk assessment of bankruptcy, the creditworthiness or the investment attractiveness of the enterprise, the financial status of the beneficiary of the investment project or enterprise subject to privatization), they are based on the assessment of the solvency of the enterprises as an indicator of its financial capacity. The main methodological problems of construction of the scorecard are formulated as one of the most important elements of the methodology of analysis, which has a significant impact on the reliable and objective assessment of the solvency of the company in accordance with the set goal. The comparative analysis of the indicators of solvency of enterprises, which are given in typical methodological approaches, is carried out in the article. It is established that the list, names and calculation formulas of the relative indicators differ significantly, and between their recommended values there are some inconsistencies, which make significant influences on the formulation of analytical conclusions and proposals for management decisions. The main signs of loss or restoration of solvency, as well as types of insolvency: current, critical, supercritical are characterized. The basic ways of streamlining and improvement of the methodological approaches of the analysis of solvency of the enterprise with the purpose of eliminating the possibility of manipulation of the analysis results are substantiated. The author propos to create a state coordination body to improve the methodological support of financial analysis of the activities of business entities in order to increase its objectivity and effectiveness.